ENGLISH NATIONAL FOLKLORE (BASED ON FOLK TALES) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
Naturally, the choice of the project topic is determined by the relevance of studying folklore from different countries (in our case, British folk tales). In English lessons, we study the grammatical structure of the language and the basic vocabulary, but it is important to have an idea about the culture of another people who speak this language. Schoolchildren are not familiar with the literary heritage of the British, namely folk tales, so the idea came up to create a product that would introduce students of our school to the oral folk art of Great Britain and, of course, would broaden their horizons in this matter.